Religion(en) im Mittelalter und der Frühen Neuzeit - Ulrike Kollodzeiski (Zeitschrift für Junge Religionswissenschaft)
Anyone applying the category of religion to medieval and early modern Europe faces difficulties similar to those of approaching religion in non-European contexts. People of earlier periods did not share our modern notion. They used comparable concepts but not identical ones. In my article, I will introduce three of them: fides, lex, and natio, and discuss their relevance for the study of religion from a modern perspective. To place these concepts in a wider context I will discuss some major differences between religion in medieval and early modern Europe in contrast to Modernity first.